(untitled) - Wetzel, Robert G. (San Diego, CA, 2001)
This newest edition is marked not only by substantial reworking, updating, and addition but also by the maturation of the author's understanding of freshwater ecosystems, and understanding that has been amassed from years of study and analysis of his own and others' research. ...the author's ability to put the tremendous array of subjects into context is nothing short of remarkable. ...this book is a timely and masterful revision, and it should be on the shelf and in the classroom of every practicing freshwater algal ecologist and limnologist
Các hệ sinh thái thủy vực,Các hệ sinh thái thủy vực
Keywords: Limmonology